Chapter 1 Introduction - Balme, Christopher B. (Taylor & Francis, 2024)
The introduction outlines the main trajectories of the Cultural Cold War, starting with the revelations in the late 1960s that the CIA was using various front organizations to fund culture abroad as a way to combat Soviet influence. It adds to the familiar narrative by showing that the Cultural Cold War needs to be re-evaluated on the one hand by focusing on US philanthropy in the postcolonial world. On the other hand there is a need to examine Soviet and East European initiatives in the newly independent nations from the perspective of cultural diplomacy and soft power. The activities on both sides of the Iron Curtain testify to the recognition on the part of US policy makers that the emerging postcolonial world needed substantial investment in cultural infrastructure if it was to resist the blandishments of socialism, to which many of its leaders were ideologically attracted, if not aligned. The final section outlines the four sections that structure the volume: Networks and Institutions; Cultural Diplomacy; Artists and Agency; and Cultures of Things.